Reflective Processes and Social Orientation at Different Stages of Professionalisation (on the Example of Preparation for Medical Activity) - G. V. Manuilov; G. G. Gorelova; E. A. Rylskaya; S. V. Morozova; N. N. Vasyagina (Russian State Vocational Pedagogical University, 2020)
Introduction. In recent decades, competency-based approach is considered to be the leading one in the system of vocational education in Russia. However, the preparation for future employment cannot be limited to competencies. This is particularly true for anthropocentric professions, for example, the training of medical workers. In such fields of employment, the personal qualities of a specialist are extremely important, i. e. his or her ability to communication, productive interaction, which implies a certain type of reflection.The aim of the present research was to identify the role of reflection, when forming the social orientation of physicians at different stages of their specialty training and realisation of oneself in this or that specialty - from university education to the end of career.Methodology and research methods. In the course of the research, psychodiagnostic methods based on the questionnaire "Differential Type of Reflection" by D. A. Leontiev et al. and FIRO - Fundamental Interpersonal Relations Orientation questionnaire by A. Schutz in the adaptation of A. A. Rukavishnikov were employed, taking into account the key provisions of theories concerning personality psychology and social behaviour. Automated neural networks based on the architecture of a multilayer perceptron according to the type of regression analysis and analysis of Kendall's tau correlation coefficient were used to process the data.Results. Reflective processes among future physicians and physicians-practitioners were studied on the sample of 384 people (aged from 17 to 76 years old) - 169 students of medical universities and 215 employees of stationary and outpatient clinics of Chelyabinsk region. It was revealed that at different stages of mastering the profession, the level of productive (systemic) reflection turned out to be different, but it was growing according to the increased degree of professionalisation. However, this level did not reach normative values in all groups, pointing to the need for psychological correction of self-determination and self-distancing. The identified ways of respondents' social orientation demonstrate the contradictory nature of relations to oneself and to others; and such relations were mostly expressed at the beginning of training. Along with the fear of being rejected, manifested at an unconscious level, the respondents took the conscious decisions to preserve own individuality and to maintain the distance with other people. This contradiction means the presence of intra-personal conflict, which, like dissatisfaction with individual needs for interpersonal communication, provokes the prevalence of unproductive types of reflection - introspection and quasi-reflection.Scientific novelty. The integration of ideas about the role, structure, content and determinants of reflection can be represented as follows: traditional understanding from the perspective of inter-individual approach as a mechanism of social perception and interpretation from the point of view of intra-individual (personal) and subject-activity approaches as the higher mental process, which is formed in the process of the acquired profession. This integration allowed the authors to identify the relationships between the level of reflection development, personal peculiarities, experience and medical specialisation.Practical significance. The research materials and the authors' conclusions can serve as a basis for the development of recommendations for the correction and prevention of unproductive forms of reflection at the initial stages of education in a medical university (e.g. specially organised extracurricular classes), as well as in the system of advanced training of practicing physicians.